PERILAKU REMAJA DALAM BERMAIN ONLINE GAME DI YOGYAKARTA - Hutasoit, Masta; Alpazara, Herian (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: The development of technologies have progressed very rapidly, one of them is online game. Online games have an impact that makes users addicted to playing it, such as increased aggressiveness in adolescents, disruption of sleep patterns, lack of concentration, socialization, and lack of empathy.. Objective: To describe the playing behavior of online games in adolescents Methods: This research was descriptive research. Purposive sampling technique with 56 students in Yogyakarta. The instrument in this study used questionnaire. Analysis statistic used univariate analysis with frequency distribution of each variable. Results: The results of the study showed that online gaming behavior in adolescents was included in the high category of (46.4%). The age of the first time playing online games was 12 years (44.6%), media games used mobile phones (80.4%), playing online games was with friends (64.3%). The type of game used was mostly aggression (87.5%). And most of the games were at home, namely (92.9%). The intensity of playing online games most of the respondents included in the category were always (39.3%). Conclusion: high category in playing games in adolescents can have an impact on needed attention to parents to monitor teenagers in playing games so as not to become addictive and have an impact on children's lives Keywords: Adolescents, Behavior, Online games